Fungal Agents Causing Chronic Otitis Externa with Their Antimicrobial Susceptibility Pattern at RMCH (TAJ: Journal of Teachers Association, 2023)
Background: Otomycosis is a well prevalent disease (9-30%) in our country which even might persist for more than 3 months (chronic cases). Now a days, development of antimicrobial drug resistant making difficult to treat such patients all over the world.Objective: To identify fungal agents causing chronic otitis externa with their antimicrobial susceptibility in Rajshahi Medical College Hospital.Material and Method: This cross-sectional descriptive study was conducted from January 2022 to December 2022 in the department of Microbiology at Rajshahi Medical College, Rajshahi. About 110 suspected chronic otitis externa patients were selected from outpatient department of ENT of RMCH & data were collected by a semi structured questionnaire. Fungal organisms isolated and identified by culture, LPCB stain and relevant tests including a specific Czapek Dox Agar media. Antimicrobial susceptibility was done by modified Kirby Bauer disc diffusion method. Data were analyzed using SPSS (version 24.0). Statistical significance was considered when p value < 0.05.Result: In this study, near half (48.18%) aural swab from respondent of chronic otomycosis were culture positive for different fungal species. Among all, A. niger was most common species (50.9%) & 1/5th of them was C. albicans (20.8%) along with other species. Most sensitive drug for different fungal species were voriconazole &itraconazole and most resistant drug were fluconazole and ketoconazole.Conclusion: As common antifungal drugs are resistant to different fungal species & their susceptibility pattern are changes day by day, among otomycosis patients the fungal culture & antimicrobial susceptibility should be done to reduce the morbidity of such patients as well as to reduce the generation of new resistance to antifungal drugs.TAJ 2023; 36: No-2: 185-192